Model pembelajaran cooperatif learning tipe STAD dalam pelajaran matematika untuk meningkatan motivasi dan prestasi belajar - Hayati Hayati (Research and Social Study Institute, 2019)
Penelitian ini bertujuan untuk mengetahui efektifitas model pembelajaran Kooperatif Tipe Student Teams Achievement Divisions (Stad) dalam meningkatkan motivasi dan prestasi belajar matematika di SDN Niten Tahun pelajaran 2017/2018. Jenis penelitian ini adalah penelitian Tindakan Kelas (PTK). Hasil penelitian menunjukkan bahwa peningkatan motivasi belajar peserta didik terhadap mata pelajaran matematika terlihat dari meningkatnya skor, dari 95 % siklus I ke 100% siklus II. Peningkatan prestasi belajar terlihat dari hasil post tes yaitu nilai rata-rata di atas KKM 75, pada siklus I 86,6 dan siklus II 82,45. Ketuntasan pada siklus I 90 % dan pada siklus II 80 %.Proses pembelajaran matematika dengan melalui penerapan model pembelajaran kooperatif learning tipe STAD terbukti dapat meningkatkan motivasi belajar,dan prestasi belajar peserta didik kelas VI SD Negeri Niten tahun Pelajaran 2017/2018. Cooperative learning model type STAD in mathematics lesson to improve learning motivation and learning achievement AbstractThis study aims to determine the effectiveness of cooperative learning model type Student Teams Achievement Divisions (STAD) in improving motivation and achievement of mathematics learning at SDN Niten 2017/2018 academic year. The type of this research is Classroom Action Research (PTK). The results show that the application of cooperative learning model type STAD can improve motivation and learning achievement in mathematics learning. The learning motivationimprovement is seen from theincrease of students’ scores, from 95% cycle I to 100% cycle II. The learning achievement improvement is seen from the post test result with mean valueabove the minimum passing grade 75, at cycle I is 86,6 and cycle II is 82,45. The completeness in cycle I is 90% and in cycle II is 80%. The application of cooperative learning model Type STAD in mathematics learning has been proven to increase learning motivation and learning achievement of sixth grade students of SD Negeri Niten 2017/2018 academic year.